Perioperative quality assurance in neurosurgery - Sjåvik, Kristin (UiT The Arctic University of Norway, 2018)
Paper I of this thesis is not available in Munin: Assessment of drainage techniques for evacuation of chronic subdural hematoma: a consecutive population-based comparative cohort study. Sjåvik K., Bartek J., Sagberg, L.M., Henriksen, M.L., Gulati, S., Ståhl, F.L., Kristiansson, H., Solheim, O., Förander, P., Jakola, A.S. Available in Journal of Neurosurgery. 2017 Jun;23:1-7 Abstract Background Perioperative treatment for common neurosurgical conditions such as chronic subdural hematomas (CSDH) and meningiomas vary. The perioperative period is by definition the time span from 24 hours before surgery until 30 days postoperatively. Even if the surgical treatment in the operation theater can be exactly the same, complication rates differ, and results vary. The aim of the thesis was to compare recurrences after CSDH burr-hole surgery using three different drainage techniques, to establish the risk of recurrence in CSDH patients using antithrombotic (AT) medication, to clarify the risk/benefit ratio of prophylactic pharmacotherapy initiated the evening before craniotomy for meningioma, and to identify important predictors for complications in meningioma surgery. A future more large-scale aim was to clarify whether this pragmatic research design could be used for further quality work in practical neurosurgery. Methods A comparative effectiveness framework was created to conduct retrospective reviews in different Scandinavian cohorts from three different neurosurgical departments (Karolinska University Hospital, University Hospital of North Norway and St. Olavs University Hospital). The Scandinavian cohorts were all population-based, and all patients treated between 2005 and 2013. Studies included large number of patients ranging from 763 to 1260 patients. Results Active subgaleal drainage for 24 hours after surgery seems to be the most efficient and safest treatment strategy for chronic subdural hematoma. Patients with CSDH on antithrombotic therapy at the time of diagnosis, have similar recurrence rates and ...